Can We Grow Shallot (Allium ascalonicum L.) Root in Hydroponic System with Simple Growing Media? - Fanny, Trio; Eliyani, Eliyani; Kurniadinata, Odit Ferry (Journal of Tropical Horticulture, 2020)
Unlike conventional agriculture, urban hydroponics are widely on a small yard scale. Hydroponics is a term used for farming without using soil as a growth medium. Plants can be planted in pots or other containers using water and other porous materials as growing media. Cheap, easily obtainable, and efficient growing media types are needed for urban communities to cultivate vegetable crops, especially shallots (Allium ascalonicum L.). Shallots have an important meaning, both in terms of high economic value and their nutritional content. It is unknown if the shallots are cultivated in a hydroponic system and how the performance of its roots and the suitable simple growing media for growing shallots in hydroponic will be enhanced. Therefore, this research was conducted to study the performance of shallot roots in several alternative hydroponic media and obtain growing media that can provide the best growth on the performance of shallot roots in the hydroponic system. The experiment was conducted in 3 months at the Glass House and Integrated laboratory of the Faculty of Agriculture, Mulawarman University, Indonesia. This research was arranged in a Randomized Block Design (RBD) with four replications. The factor is the growing media (m) which consists of 4 levels, namely: m1 = sand (± 80-100 mesh); m2 = burnt rice husk; m3 = egg cartons; and m4 = wood shavings (± 90-120 mesh). Data retrieval by observing the following parameters: Leaf length (cm), Number of leaves (strands), Number of plant bulbs (bulbs), bulbs wet weight (grams), bulbs dry weight (grams), Longest root length (cm), and Total root length (m). This research showed that the burnt rice husk and wood shavings growing media influence the growth and performance of the shallots' roots (Allium ascalonicum L.) plants and can be used as the simple growing media in urban hydroponic as Household scale cultivation. On the other hand, the growing media from sand and egg cartons are not recommended for growing shallots in the hydroponic system.